Redundant switching state based DTC for six‐phase symmetrical induction motor driven by nine‐switch inverter. Issue 12 (12th November 2019) - Sharma, Sohit; Aware, Mohan; Bhowate, Apekshit
Abstract : This paper presents the implementation of direct torque control (DTC) algorithm on the symmetrical six‐phase (0° displaced) induction motor supplied by nine‐switch inverter (NSI). This configuration provides the better dc bus utilisation in comparison to symmetrical 60° displaced and asymmetrical six‐phase induction motor. In the conventional topology, 12‐switch two‐level inverter is required to control the drive where total 64 switching states are available. In the proposed system, NSI is used to drive the motor which is having 27 switching states. The DTC algorithm is proposed with five‐level torque comparator by using large, small and zero voltage vectors for reduction in torque ripples. The elimination of xy ‐subspace flux without affecting the merits of conventional DTC is achieved by using redundant switching states of the inverter. The experimental results under steady‐ and dynamic‐state operation are provided with DTC algorithm on 0° displaced symmetrical six‐phase motor supplied by NSI to validate the effective controlling.